Comparing Models with Positive Anticipated Emotions, Food Values, Attitudes and Subjective Norms as Influential Factors in Fast-Food Purchase Intention during the COVID-19 Pandemic in Two Channels: Restaurants and Mobile Apps - María Núñez-Fernández (MDPI AG, 2021)
The purpose of this research is to determine if positive anticipated emotions, food values, attitudes and subjective norms influence food purchase intention in two different models: a fast food restaurant and a food delivery service via mobile apps. For this study, we utilized a non-experimental, causal, descriptive and cross-sectional design. From October 2020 to January 2021, self-administered online surveys were distributed to a convenience sample of 200 fast-food consumers at restaurants, and users of food delivery services via mobile apps Puebla City, Mexico. IBM–SPSS Statistics and the SmartPLS 3 Partial Least Squares Structural Equation Modeling were used to test our hypotheses. The results underscored a difference in attitudes between the models. The attitude toward the brand positively and significantly influenced purchase intention via mobile apps, whereas attitude toward eating a hamburger positively and significantly influenced purchase intention of visiting a fast-food restaurant. In both models, positive anticipated emotions exhibited the closest relationships with purchase intention, attitude toward the brand and attitude toward eating a hamburger, whereas food values exerted an insignificant effect on attitudes and purchase intention. Future research should consider performing a face-to-face survey with a random sample while accounting for different demographics, regions and countries, as well as including other brands, food types and restaurants.